‘Unequal mobilities’ in the Lisbon Metropolitan Area: daily travel choices and private car use - Carmo, R. M. (2017)
Mobilities have been looked at in increasingly greater depth over the last few decades, posing a growing set of theoretical and methodological problems for urban studies. One of the approaches that are being taken in this field is to consider the relationship between social inequalities and the various different mobility conditions. The present article seeks to show the extent to which mobility behaviours of Lisbon Metropolitan Area residents vary in accordance with a range of inequality variables, such as gender, education, social class, and age, thus generating clearly marked social profiles. Special attention is paid to car use. Statistical analysis of a questionnaire applied to 1,500 residents shows that regular car use is still relatively circumscribed to one social group, to which it offers the advantage of less time spent on daily travel, notwithstanding the increased costs. On the other hand, populations who regularly use public transport are at a disadvantage, spending more of their day travelling from one place to another.